Psychological Analysis Of Behavioral Characteristics In Adaptation To Social Life Of Family-Type Caregivers Of Children - Dear Torakulov L Tirkashevych (Open Academia, 2024)
This article highlights the results of a scientific study conducted to study the behavioral characteristics of children from or p hanages in the process of their adaptation to social life.
Keywords: Competition; adaptation; compromise; agreement